2014
DOI: 10.1111/imm.12337
|View full text |Cite
|
Sign up to set email alerts
|

Both plasmacytoid dendritic cells and monocytes stimulate natural killer cells early during human herpes simplex virus type 1 infections

Abstract: SummaryHerpes simplex virus type 1 (HSV-1), a member of the herpes virus family, is characterized by a short replication cycle, high cytopathogenicity and distinct neurotropism. Primary infection and reactivation may cause severe diseases in immunocompetent and immunosuppressed individuals. This study investigated the role of human plasmacytoid dendritic cells (pDC) in the activation of natural killer (NK) cells for the control of herpesviral infections. Within peripheral blood mononuclear cells, UV-inactivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…An increase in the HLA-E expression on the cell surface has been shown in monocytes activated by different stimuli, such as IL-27 or IFN-a [35,36]. Accordingly, the expression of HLA-E was low in primary monocytes and strongly up-regulated in MDMs.…”
Section: Discussionmentioning
confidence: 95%
“…An increase in the HLA-E expression on the cell surface has been shown in monocytes activated by different stimuli, such as IL-27 or IFN-a [35,36]. Accordingly, the expression of HLA-E was low in primary monocytes and strongly up-regulated in MDMs.…”
Section: Discussionmentioning
confidence: 95%
“…IL-18 produced from activated macrophages induced IFN-γ production by NK cells and protected mice from HSV infections [32]. IFN-γ is also produced from activated macrophages and γδ T cells in response to HSV infections, which further stimulates macrophages to produce TNF-α, which activates NK cells for HSV control [33]. Depletion of macrophages with clodronate liposomes or modulation of the tumor microenvironment with CPA (reducing IFN-γ expression and infiltration of macrophages) improves oHSV intratumoral spread and efficacy in brain tumors [34].…”
Section: Host Responses Against Hsv Infectionmentioning
confidence: 99%
“…In particular, it was shown that functional interactions between DCs and NK cells occur. DCs are required for Ly49H + NK cell accumulation in mouse cytomegalovirus infection and for proper NK cell response in Herpes simplex virus‐1 infection …”
Section: The Interaction Of Nk Cells and Dendritic Cellsmentioning
confidence: 99%